2010
DOI: 10.4081/ijas.2010.e71
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels of copper on growth performance and cecal ecosystem of newly weaned piglets

Abstract: The current study aimed to investigate the effects of different levels of copper sulfate on the growth performance and cecal ecosystem in newly weaned piglets. One hundred piglets weaned at 28±2 d were randomly allocated to 4 treatments with 5 replicates of 5 piglets each. Piglets received for 28 d the base diet with i) no addition (control) or with copper addition (from copper sulfate) at ii) 100, iii) 175, and iv) 250 mg/kg -1 . On day 21, twenty piglets were randomly selected (one from each replicate) to sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 14 publications
5
16
1
Order By: Relevance
“…In study P69 (Ma et al, 2007) no effect of addition of 49 mg/kg Cu as CuMM was detected on the population of lactobacilli in content from the SI or colon. In study P72 (Mei et al, 2010) a numeric reduction in the population of lactobacilli was detected by addition of 100, 175 and 250 mg/kg Cu as CuSO 4 to piglet diets when the population density were enumerated using selectively cultivation, however if the population of lactobacilli were quantified by use of qPCR the reduction found for 175 and 250 mg/kg Cu as CuSO 4 were significant different from the results found in the control fed piglets.…”
Section: Bbjmentioning
confidence: 73%
See 3 more Smart Citations
“…In study P69 (Ma et al, 2007) no effect of addition of 49 mg/kg Cu as CuMM was detected on the population of lactobacilli in content from the SI or colon. In study P72 (Mei et al, 2010) a numeric reduction in the population of lactobacilli was detected by addition of 100, 175 and 250 mg/kg Cu as CuSO 4 to piglet diets when the population density were enumerated using selectively cultivation, however if the population of lactobacilli were quantified by use of qPCR the reduction found for 175 and 250 mg/kg Cu as CuSO 4 were significant different from the results found in the control fed piglets.…”
Section: Bbjmentioning
confidence: 73%
“…Quantitative real-time polymerase chain reaction (qPCR) has been used in one investigation with piglets (P72, Mei et al, 2010) to detect the effect of copper supplementation on bacterial populations (lactobacilli, enterobacteria or total anaerobic bacteria) in gastrointestinal content. It was shown that The present document has been produced and adopted by the bodies identified above as author.…”
Section: Use Of Qpcr To Quantify Microbial Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparably, the dose range of CuSO 4 , which significantly improved growth performance in pigs was typically higher at 100 to 250 mg/kg [3,17,18]. Furthermore, another study predicted that peak ADG and ADFI in weaned pigs were obtained with supplemental Cu levels at 150 and 114 mg/kg, respectively, in the form of CuSO 4 [19].…”
Section: Discussionmentioning
confidence: 99%